Dual processing of sulfated steroids in the olfactory system of an anuran amphibian - Sansone, Alfredo; Hassenklöver, Thomas; Offner, Thomas; Fu, Xiaoyan; Holy, Timothy E.; Manzini, Ivan (Frontiers in Cellular Neuroscience, 2015)
Chemical communication is widespread in amphibians, but if compared to later diverging tetrapods the available functional data is limited. The existing information on the vomeronasal system of anurans is particularly sparse. Amphibians represent a transitional stage in the evolution of the olfactory system. Most species have anatomically separated main and vomeronasal systems, but recent studies have shown that in anurans their molecular separation is still underway. Sulfated steroids function as migratory pheromones in lamprey and have recently been identified as natural vomeronasal stimuli in rodents. Here we identified sulfated steroids as the first known class of vomeronasal stimuli in the amphibian Xenopus laevis. We show that sulfated steroids are detected and concurrently processed by the two distinct olfactory subsystems of larval Xenopus laevis, the main olfactory system and the vomeronasal system. Our data revealed a similar but partially different processing of steroid-induced responses in the two systems. Differences of detection thresholds suggest that the two information channels are not just redundant, but rather signal different information. Furthermore, we found that larval and adult animals excrete multiple sulfated compounds with physical properties consistent with sulfated steroids. Breeding tadpole and frog water including these compounds activated a large subset of sensory neurons